Hybrid active/passive force control strategy for grinding marks suppression and profile accuracy enhancement in robotic belt grinding of turbine blade. (February 2021) - Xu, Xiaohu; Chen, Wei; Zhu, Dahu; Yan, Sijie; Ding, Han
Highlights: An active force control consisting of force/positon and PI/PD controller based on six-dimensional force/torque sensor is introduced to eliminate the grinding marks and traces, and a passive force control including PID controller based on one-dimensional force sensor is proposed to reduce the over- and under-cutting phenomenon in robotic machining system. The Kalman filter information fusion methodology is adopted to combine the active and passive force control methods which could improve the controlled force accuracy and efficiency, as well as avoid the control interference. Experiments on the test workpiece and turbine blade are employed to verify the reliability and practicality of the proposed hybrid force control method on the aspect of grinding marks and traces suppression, surface quality and profile accuracy enhancement. Abstract: Grinding marks and traces, as well as the over- and under-cutting phenomenon are the severe challenges in robotic abrasive belt grinding of turbine blades and it greatly limits the further application of robotic machining technology in the thin-walled blade fields. In the paper, an active force control method consisting of force/positon and PI/PD controller based on six-dimensional force/torque sensor is introduced to eliminate the grinding marks and traces, and a passive force control method including PID controller based on one-dimensional force sensor is proposed to reduce the over- and under-cutting phenomenon in robotic machining system. Then the Kalman filter information fusion methodology is adopted to combine the active and passive force control methods which could improve the controlled force accuracy and efficiency, as well as avoid the control interference. Finally both the test workpiece and turbine blade are employed to examine and verify the reliability and practicality of the proposed hybrid force control method by achieving the desired surface quality and higher profile precision.